2015
DOI: 10.1039/c5sc01467k
|View full text |Cite
|
Sign up to set email alerts
|

Iron catalyzed CO2hydrogenation to formate enhanced by Lewis acid co-catalysts

Abstract: Iron/Lewis acid co-catalysts hydrogenate to CO2 to formate with unprecedented turnover for a first row transition metal catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
272
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(282 citation statements)
references
References 66 publications
7
272
1
2
Order By: Relevance
“…The diiron complexes with bridging hydrides reported by Holland and Limberg react with two equivalent of CO 2 to form two µ‐1,3‐formate donors over a 20 h reaction time,, corresponding to estimated pseudo first order rate constants of which are approximately an order of magnitude faster than our case for the combined first and second hydride transfer steps. The CO 2 insertion rates of these reported hydridoiron β‐diketiminate complexes are themselves two orders of magnitude smaller than those for pincer complexes; for example, one (PNP)FeCO dihydride complex reacts to completion within 25 min and has been calculated to proceed by an outer‐sphere pathway , . The tripodal phosphane‐ligated iron hydride reacts to completion with CO 2 in 12 h; the lower limit for the estimated rate constant is comparable to 1 .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The diiron complexes with bridging hydrides reported by Holland and Limberg react with two equivalent of CO 2 to form two µ‐1,3‐formate donors over a 20 h reaction time,, corresponding to estimated pseudo first order rate constants of which are approximately an order of magnitude faster than our case for the combined first and second hydride transfer steps. The CO 2 insertion rates of these reported hydridoiron β‐diketiminate complexes are themselves two orders of magnitude smaller than those for pincer complexes; for example, one (PNP)FeCO dihydride complex reacts to completion within 25 min and has been calculated to proceed by an outer‐sphere pathway , . The tripodal phosphane‐ligated iron hydride reacts to completion with CO 2 in 12 h; the lower limit for the estimated rate constant is comparable to 1 .…”
Section: Resultsmentioning
confidence: 90%
“…Although tempting to draw conclusions on mechanism as either inner or outer sphere from this literature comparison, this analysis is arguably complicated by the relative bond dissociation free energies for the differing M–H species. We sought then to compare our values to those for reported iron hydride species , . To our knowledge, no such kinetic study has been reported for an iron hydride complex.…”
Section: Resultsmentioning
confidence: 99%
“…The proton NMR shift of the N−H proton is an indicator of the strength of the hydrogen bonding, with further downfield shifts indicating stronger interactions. 15 The similarity in the N−H shift in compounds 2 and 3 indicates similar hydrogen-bonding interactions in solution. From this we propose that 2 is monomeric in solution and dimerizes upon crystallization.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…[89] Hazari/Bernskoetter and co-workers showed that Fe-30, especially in the presence of aL ewis acid, such as LiOTf, catalyzes the hydrogenation of CO 2 highly efficiently (TON % 59 000). [90] Fe-30,a nalogous to Co-11,d oes not contain an acidic proton in the ligand. Activation of H 2 by anon-classical hydrogen complex was proposed, which gets deprotonated by the strong base DBU,l eading to am etal hydride complex.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of H 2 by anon-classical hydrogen complex was proposed, which gets deprotonated by the strong base DBU,l eading to am etal hydride complex. [83,90] In the hydrogenation of CO 2 to formate,the most efficient Fe and Mn catalysts show similar TONs,b ut Fe-mediated reactions can proceed faster.…”
Section: Methodsmentioning
confidence: 99%